POSTURAL EVALUATION IN CHILDREN OF 10 TO 14 YEARS (Fiep Bulletin - online, 2019)
This research aims to perform postural assessment in children aged 10 to 14 years and to identify possible posturaldeviations, probable changes in the boys and girls column, as well as to verify the index of which genders are most affected bypostural deviations and orientation good posture. Participants were 18 children of both sexes with ages varying between 10 and14 years enrolled in a public school in the city of Novo Aripuanã / AM. The subjects were separated in pairs (of the same sex) forthe accomplishment of the evaluation by photogrammetry, which consists of the capture of images and launched to the programSAPO (Software of Postural Evaluation) to analyze the obtained data. Styrofoam balls of 20 mm were fixed in the evaluated, bymeans of adhesive tape, as a way of identifying the points to be analyzed. The evaluated ones were placed in an anatomicalposition and photographed in anterior, posterior and lateral view (right and left). They were dressed in clothing that made itpossible to see the upper and lower limbs. It was observed that 9 individuals presented postural deviations; among the 9 withdeviation, the majority were boys, 11 boys (n = 61.1%) and 7 girls (n = 38.9%). Some of the evaluated ones presented deviationslike hiperlordose, hypercifose, scoliosis. As a result, we obtained 3 individuals (16.6%) with hyperlordosis, 2 boys (66.7%) and 1girl (33.3%); 5 (27.8%) with scoliosis, 3 boys (60%) and 2 girls (40%); 1 boy (5.6%) with hyperkyphosis and 9 (50%) individualswithout changes, 5 boys (55.6%) and 4 girls (44.4%); none of the patients had more than one deviation.
Keywords: Postural Assessment; Posture; Vertebral Column